Formation of desired values: the role of parents - Yusof, Selamah; Mohd Amin, Ruzita; Haneef, Mohamed Aslam; Md. Noon, Hazizan (MCB UP Limited, 2002)
This study investigates the values of teenagers and their parents, and the influence parents have on the values of their children. Values are categorized into terminal and instrumental values. Different from previous works on values, the measurement of both these values is based on al-Ghazali's works in line with Islamic ethics. In addition, this study also determines the "oughtness" of both categories of values. The results reveal that overall, both teenagers and parents had good instrumental and terminal values. However, there were differences in the terminal values of teenagers and parents across ethnic groups. The analysis also shows that teenagers shared similar terminal and instrumental values as their parents, implying that parents had a significant influence on the development of their children's values. Thus parents play an important role in transmitting good values to their children in resisting negative influences.